Detection of torque teno sus virus infection in Indian pigs - Subramanyam, V.; Hemadri, D.; Kashyap, S.P.; Hiremath, J.; Barman, N.N.; Ralte, E.L.; Patil, S.S.; Suresh, K.P.; Rahman, Habibur (Veterinary World, 2019)
Background and Aim: Torque teno viruses (TTVs) are circular, single-stranded DNA viruses, which infect a wide range of animals including livestock and companion animals. Swine TTVs (torque teno sus viruses [TTSuVs]) are thought to act as a primary or coinfecting pathogen in pathological conditions such as porcine dermatitis and nephropathy syndrome and post-weaning multisystemic wasting syndrome. So far, the presence of the virus has not been reported in India. Considering that TTSuVs have the potential to cross the species barrier into humans and that pork consumption is common in North-Eastern states of India, the current study aims to investigate the presence of TTSuV in the Indian pig population. Materials and Methods: A total of 416 samples were collected during 2014-2018, from both apparently healthy pigs and also from pigs suspected of having died from classical swine fever and/or porcine reproductive and respiratory syndrome. These samples were screened for TTSuV infection by polymerase chain reaction (PCR) and DNA sequencing techniques. Results: The presence of the virus was confirmed in 110 samples from 12 different states of India. Phylogenetic analysis of the nucleotide sequences obtained from the PCR products indicated the presence of viruses of both Iotatorquevirus and Kappatorquevirus genera in India. Conclusion: The study is the first report on the presence of TTSuVs in India and highlights the circulation of both genera of the virus in the country.